2004
DOI: 10.1017/s0263574703005460
|View full text |Cite
|
Sign up to set email alerts
|

Tracking a joint path for the walk of an underactuated biped

Abstract: This paper presents a control law for the tracking of a cyclic reference path by an under-actuated biped robot. The robot studied is a five-link planar biped. The degree of under-actuation is one during the single support phase. The control law is defined in such a way that only the geometric evolution of the biped configuration is controlled, but not the temporal evolution. To achieve this objective, we consider a parametrized control. When a joint path is given, a five degree of freedom biped in single suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 10 publications
1
63
0
Order By: Relevance
“…The torques Γ are bounded, thus they do not affect the instantaneous double support. The impact model can be written as (8):…”
Section: Impact Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The torques Γ are bounded, thus they do not affect the instantaneous double support. The impact model can be written as (8):…”
Section: Impact Modelmentioning
confidence: 99%
“…Thus the system is under-actuated and its motion cannot be freely chosen. Studies of control of such an underactuated biped (6), (8) have shown that a geometric evolution of the robot q(s) can be chosen. For a given function q(s) within some limits, function s(t) defining a motion compatible with the dynamic model can be deduced using equation (11).…”
Section: The Foot-rotation Sub-phasementioning
confidence: 99%
“…Though not indicated in the figure, massless springs may be attached between links and between links and the inertial reference frame; prismatic joints between links are also allowed. This class of systems clearly includes the Acrobot [2,36,52], the brachiating robots of [15,34,35,46], the gymnast robots of [32,39,57] when pivoting on a high bar, and the stance phase models of Raibert's onelegged hopper [1,6,14,26,33,42] as well as RABBIT [7][8][9][10]41]. The control objectives will be to stabilize the system about an equilibrium point or to track a set of reference trajectories with internal stability.…”
Section: Motivating Classes Of Systemsmentioning
confidence: 99%
“…In the above, note that σ, given by (9), is the usual angular momentum of the robot about the attachment point. Since the robot is constrained to a horizontal plane, if the spring constant were zero, then angular momentum would be conserved and asymptotic stabilization to an equilibrium point would be impossible.…”
Section: ) Mathematical Representationmentioning
confidence: 99%
See 1 more Smart Citation